Isolation and Characterization of High-Efficiency Rhizobia From Western Kenya Nodulating With Common Bean - Wekesa, Clabe Simiyu; Furch, Alexandra C. U.; Oelmüller, Ralf (Frontiers in Microbiology, 2021)
Common bean is one of the primary protein sources in third-world countries. They form nodules with nitrogen-fixing rhizobia, which have to be adapted to the local soils. Commercial rhizobial strains such as R. tropici CIAT899 are often used in agriculture. However, this strain failed to significantly increase the common bean yield in many places, including Kenya, due to the local soils' low pH. We isolated two indigenous rhizobial strains from the nodules of common bean from two Western Kenya's fields that have never been exposed to commercial inocula. We then determined their ability to fix nitrogen in common beans, solubilize phosphorus and produce indole acetic acid. In greenhouse experiments, common bean plants inoculated with two isolates, B3 and S2 in sterile vermiculite, performed better than those inoculated with CIAT899 or plants grown with nitrogen fertilizer alone. In contrast to CIAT899, both isolates grew on media with pH 5. Furthermore, isolate B3 had higher phosphate solubilization ability and produced more indole acetic acid than the other two rhizobia. Genome analyses revealed that B3 and S2 are different strains of Rhizobium phaseoli. We propose that the two indigenous rhizobial strains from Kenya are ideal inocula for common bean production in countries with acid soils.